Вплив рівня примативності на професійну орієнтацію молодих фахівців - Ковальова, Олена (Видавництво Національного університету "Львівська політехніка", 2009)
Is examined the problem of motivation of choosing profession by a young man. This problem is examined from the point of view the instinctive models of behavior, namely hierarchical instinct which is basis of construction of social intercommunications in society.
Keywords: hierarchical instinct; primativity; instinctive psychology; prevailing-submission; social intercommunications